1991
DOI: 10.1111/j.1442-200x.1991.tb01517.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Upper Gastrointestinal Endoscopy in Japanese Children

Abstract: A total of 370 children who underwent upper gastrointestinal endoscopy (534 procedures) were retrospectively studied. All procedures were performed successfully. Side effects were demonstrated in only one case (0.2%), which was complicated by perioral cyanosis during the procedure. As to preendoscopic medication, it was thought that topical pharyngeal anesthesia alone may well be used for school‐age children over 7 years of age, general anesthesia with endotracheal intubation for neonates, and intravenous seda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In western countries, the most common reported causes are gastric and duodenal ulcers, esophagitis, gastritis and varices, while in India, variceal bleeding predominates. 4,[9][10][11][12][13] In this study, the most common cause of upper GI bleeding in children was gastric erosions which is similar to other studies. 3,5 (Table 2) There are only two reports from India in which the main cause of upper GI bleeding in pediatric patients was esophageal varices and thus they concluded that the cause of upper GI bleeding is different between developed and developing countries 4,11 , but the present study showed that this conclusion is not a fact in every developing country, because the causes of upper GI bleeding in present study are similar to developed countries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In western countries, the most common reported causes are gastric and duodenal ulcers, esophagitis, gastritis and varices, while in India, variceal bleeding predominates. 4,[9][10][11][12][13] In this study, the most common cause of upper GI bleeding in children was gastric erosions which is similar to other studies. 3,5 (Table 2) There are only two reports from India in which the main cause of upper GI bleeding in pediatric patients was esophageal varices and thus they concluded that the cause of upper GI bleeding is different between developed and developing countries 4,11 , but the present study showed that this conclusion is not a fact in every developing country, because the causes of upper GI bleeding in present study are similar to developed countries.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple reports have established its safety norms in children. 4,12,[17][18][19] In the present study, the cause of bleeding could not be ascertained in 20.5% of cases. This may be due to some delay in performing endoscopy or some cases of esophageal or gastric erosions which got healed up rapidly before being confirmed by endoscopy.…”
Section: Discussionmentioning
confidence: 88%
“…In general, the procedure is regarded as very safe, with published complication rates less than 1.7%. 9,10 Serious complications related to endoscopic technique are rare. 1,2 These include mucosal tear, perforation, haemorrhage, pancreatitis, transmitted infection and retropharyngeal haematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal pain was the sole indication for endoscopy if it was localized to the epigastrium and associated with tenderness. Premedication for endoscopy was as described previously [11]. Sigmoidoscopy using Olympus PCF type 20 (Tokyo, Japan) was performed in four patients because of bloody stools.…”
Section: Offprint Requests To: S Katomentioning
confidence: 99%